2012
DOI: 10.1007/s11243-012-9576-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA-binding properties of ruthenium(II) complexes with the bidentate ligand 5-chloro-2-(phenylazo)pyridine

Abstract: A bidentate ligand, 5-chloro-2-(phenylazo)pyridine (Clazpy), and its two polypyridyl ruthenium(II) complexes, [Ru(Clazpy) 2 bpy]Cl 2 Á7H 2 O (1) and [Ru(Clazpy) 2 phen]Cl 2 Á8H 2 O (2), were synthesized and characterized. The DNA-binding properties of these complexes with DNA, the breast cancer susceptibility gene 1 (BRCA1), and the pBIND plasmid DNA were probed by photocleavage, electronic absorption titration, ethidium bromide quenching, and thermal denaturation. Both complexes were found to bind to the BRCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Platinum drugs exert their antitumor effects by binding to DNA, thereby changing the replication of DNA and inhibiting the growth of the tumor cells. For ruthenium-based drugs, there has been some evidence demonstrating an interaction between ruthenium complexes and DNAs [ 18 , 20 , 30 ]. Our previous study has demonstrated that 1 and 2 bound to the specified DNA fragment of the human breast cancer suppressor gene 1 (BRCA1) through the intercalative mode into the base pairs of DNA, and the DNA-binding constants (K b ) for 1 and 2 were 7.09 × 10 4 M -1 and 5.19 × 10 5 M -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Platinum drugs exert their antitumor effects by binding to DNA, thereby changing the replication of DNA and inhibiting the growth of the tumor cells. For ruthenium-based drugs, there has been some evidence demonstrating an interaction between ruthenium complexes and DNAs [ 18 , 20 , 30 ]. Our previous study has demonstrated that 1 and 2 bound to the specified DNA fragment of the human breast cancer suppressor gene 1 (BRCA1) through the intercalative mode into the base pairs of DNA, and the DNA-binding constants (K b ) for 1 and 2 were 7.09 × 10 4 M -1 and 5.19 × 10 5 M -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study has demonstrated that 1 and 2 bound to the specified DNA fragment of the human breast cancer suppressor gene 1 (BRCA1) through the intercalative mode into the base pairs of DNA, and the DNA-binding constants (K b ) for 1 and 2 were 7.09 × 10 4 M -1 and 5.19 × 10 5 M -1 , respectively. This data indicated that the binding affinity of these two complexes to DNA was dependent on the aromatic planarity and hydrophobicity of the intercalative polypyridyl ligand [ 18 ]. We further investigated whether the ruthenium(II) complexes with the bidentate ligand 5-chloro-2-(phenylazo)pyridine were capable of blocking BRCA1 amplification.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). The ruthenium complexes of [Ru(Clazpy) 2 (L)]Cl 2 · xH 2 O, where L is either 2,2 -bipyridine (bpy) or 1,10-phenanthroline (phen), have been studied for their DNA-binding properties 10 . However, coordination complexes of Clazpy with other metal ions are few 11 , and to our knowledge, their antimicrobial activities have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%